The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1088/0953-8984/4/40/009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of defects on the Ni 2p and O 1s XPS of NiO

Abstract: AbslracL The Ni 2p and 0 Is XPS of NiO single crystals were measured using monochromatic Al K a radiation. Different treatmenu of the crystals allow us to give a description of the influence of defects on these spectra. The Ni 2p3p spectrum of in-sirucleaved NiO exibiu clearly visible features at 854.1 eV, 855.6 eV and 861 eV The intensity ratio changes after ion bombardment and an additional peak at 852.2 eV appears. ApaR from a slight increase in linewidth the 0 1s spectrum remains unchanged. The 0 Is spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
145
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(173 citation statements)
references
References 15 publications
16
145
0
1
Order By: Relevance
“…At higher excitation energies the spectra are identical to that of Fe 3 O 4 , despite in particular for sample SN1 a weak Fe 3+ charge transfer satellite is also present at higher excitation energies indicating a small excess of trivalent ions at the interface between Fe 3 O 4 and NiO. 44 The corresponding Ni 2p spectra are overlapped by broad Fe 2s states (Figs. 2b and d).…”
Section: Resultsmentioning
confidence: 73%
“…At higher excitation energies the spectra are identical to that of Fe 3 O 4 , despite in particular for sample SN1 a weak Fe 3+ charge transfer satellite is also present at higher excitation energies indicating a small excess of trivalent ions at the interface between Fe 3 O 4 and NiO. 44 The corresponding Ni 2p spectra are overlapped by broad Fe 2s states (Figs. 2b and d).…”
Section: Resultsmentioning
confidence: 73%
“…Uhlenbrockt et al 26 investigated a pure NiO single crystal cleaved under UHV conditions and found that a perfect NiO surface exhibits the characteristic peak at 853.4 to 854.4 eV but also an additional shoulder at 855.6 eV which overlaps with the characteristic peak for Ni 2 O 3 and Ni(OH) 2 at 855.1 to 856.6 eV, 27-32 see gray areas in Figure 2. Therefore the Ni 2p spectra was fitted according to 33 with hydrogen terminated Figure 1.…”
Section: Results and Discussion -Xps Interfacesmentioning
confidence: 99%
“…Both the unthermolyzed and thermolyzed solids show peaks at about 529.5 and 531.5 eV. The low energy peak is assigned to surface lattice oxygen, and the higher energy peak to adsorbed oxygen and surface hydroxyl species at defect sites [53][54][55]. Any oxygen associated with Ni 3+ (NiO is non-stoichiometric) will also occur at about 531.5 eV [55].…”
Section: Thermolysis Processmentioning
confidence: 99%